Heterozygous Single-Nucleotide Polymorphism Genotypes at Heat Shock Protein 70 Gene Potentially Influence Thermo-Tolerance Among Four Zebu Breeds of Nigeria - Onasanya, Gbolabo Olaitan; Msalya, George Mutani; Thiruvenkadan, Aranganoor Kannan; Sreekumar, Chirukandoth; Tirumurugaan, Gopalan Krishnaswamy; Fafiolu, Adeboye O.; Adeleke, Matthew A.; Yakubu, Abdulmojeed; Ikeobi, Christian Obiora Ndubuisi; Okpeku, Moses (Frontiers in Genetics, 2021)
Genetic variants at heat shock protein 70 gene and their influence on heat stress (HS) tolerance were studied among selected Nigeria zebu, namely, 25 White Fulani (WF), 21 Sokoto Gudali (SG), 21 Red Bororo (RB), and 23 Ambala (AM). Detection of single nucleotide polymorphism (SNP) followed by determination of genotype and genotypic frequency was made among the selected breeds. The heat tolerance coefficient (HTC) was determined from thermo-related parameters including body temperature, rectal temperature, and respiratory rate. Thermo-Tolerance was evaluated through the SNP–thermo-parameter relationship. Statistical analyses were done using the GLM procedure in SAS. A quantitative real-time/high-resolution melting-based assay detected twelve genetic variants. Five of these were common and shared across all breeds of cattle. Of the remaining seven variants, three were specifically identified in AM, two in SG, and two in RB. Also, SNPs were evaluated and four unique SNPs (C151T, C146T, G90A, and C219A) were identified. Heterozygous animals had lower HTC suggesting their potential to withstand HS than homozygous counterparts. The WF and RB animals had significantly lower values for all parameters (BT, RT, RR, and HTC) compared to AM and SG breeds. Thermo-related parameters were significantly different (P < 0.001), and it is recommended that screening of SNPs in zebu is needed to enable selection for improved thermo-tolerance.